PENGARUH HARGA, KERAGAMAN PRODUK DAN DIGITAL PAYMENT TERHADAP LOYALITAS KONSUMEN PADA MINIMARKET ADEN MART DI BONDOWOSO MELALUI KEPUASAN KONSUMEN SEBAGAI VARIABEL INTERVENING - Adelia Lutfiah Sari; Ika Wahyuni; Muhammad Iqbal Anshory (Jurnal Mahasiswa Entrepreneurship (JME), 2025)
ABSTRACT Aden Mart, a local minimarket in Bondowoso, faces various challenges in maintaining its competitiveness amidst intense retail competition. The availability of non-cash payment services is still limited, making it less attractive to consumers accustomed to using e-wallets or QRIS. Meanwhile, in terms of product diversity, Aden Mart is unable to provide a complete range of goods that are in line with consumer trends, so some customers prefer shopping at other minimarkets that offer a wider selection of products. Data analysis and hypothesis testing in this study used the Structural Equation Model – Partial Least Squares (PLS-SEM). The results of the direct influence hypothesis test using the Smart PLS 3.2.8 application. The results of the study indicate that: Price and product diversity have a positive and significant effect on Consumer Satisfaction, while Digital payment has no significant effect. Price and product diversity have a positive and significant effect on Consumer Loyalty, while Digital payment has no significant effect. Consumer satisfaction has a positive and significant effect on Consumer Loyalty. Consumer satisfaction partially mediates the effect of Price and product diversity on Consumer Loyalty, but does not mediate the effect of Digital payment. This finding confirms that increasing Consumer Loyalty at Aden Mart is more effectively achieved through a competitive Pricing strategy and providing Product Diversity that suits Consumer needs, accompanied by services that can increase satisfaction.